(untitled) (Revista Argentina de Cirugía, 2022)
Competency-based education has been accepted as a teaching approach focused on outcomes of learning: knowledge, skills and attitudes that will enable the learner to effectively perform activities in a future professional environment. This is particularly appropriated for undergraduate medical students during the course of surgery. This kind of approach requires a proper evaluation to reinforce the learning process. However, competency-based evaluation involves making subjective judgment about the level of per- formance of a set of competencies. Therefore, it is important to develop precise strategies to measure different competencies. The present report describe three evaluation tools in line with the competency based teaching appro- ach: resolution of case problems, elaboration of algorithms and observation of clinical practice. These strategies allow the teaching staff to develop a formative evaluation and formal qualification.